Aplikasi Algoritma Semut Pada Penentuan Rute Terpendek Sistem Pengangkutan Sampah Kota Makassar - Nur Ahniyanti Rasyid; Dhian Eka Wijaya (Journal of Mathematics, Statistics and Applications, 2024)
Waste management is one of the problems faced by the City of Makassar, so an effective and efficient system is needed for more regular waste transportation at each TPA. This study aims to optimize the waste transportation system in Makassar City by determining the shortest route. The research method was carried out by taking 8 TPA points and determining the optimal shortest route using the ant algorithm. The ant algorithm is an algorithm adopted from the behavior of ant colonies. The application of the ant algorithm shows the result in the form of the optimal shortest route with a route length of 40.2 km with the route V5→V1→V4→V7→V6→V2→V8→V5. The calculation is based on the use of one starting point, where the starting point is the center of route determination to various landfills.